Investigation of Λ-Hypernuclei within the Equation of Motion Phonon Method. (1st March 2023) - Petrellis, D.; Veselý, P.; De Gregorio, G.; Knapp, F.; Bydžovský, P.; Denisova, D.; Pokorný, J.; Skoupil, D.; Lo Iudice, N.
Abstract: A formulation of the equations of motion phonon method (EMPM) suited for hypernuclei is outlined and illustrated through an application to B ∧ 12 . A self-consistent calculation using realistic modern potentials is performed using a multiphonon basis which enables us to couple the Λ-particle-proton-hole (pΛ - h) Tamm-Dancoff (TDΛ) states to the excitations of the nuclear core. The impact of such a coupling on the energy levels and on the electroproduction cross section of B ∧ 12 suggests that complex configurations accounting for the excitation of the nuclear core are needed for approaching the experimental data.